Il Lifelong learning: modelli a confronto, a cento anni da Democrazia e Educazione [1916] - Walter Rinaldi (Firenze University Press, 2017)
This looks at the main current Lifelong Learning educational models , in their theoretical aspects, from the guidelines outlined in "Democracy and Education" by John Dewey one hundred years ago. Afterwards their evolution in the policies of international organizations and the European Union is broadly discussed. It is then brought about the current debate, with particular regard to the stance of some significant critical opinions towards the tendency to interpret Lifelong Learning as an adjustment to the demands of market economy. Facing today great economic and social changes, a proposal is put forward focusing on the individual and citizen's educational perspectives, in the light of a critical openness to change.